Symptom Duration and Diabetic Control Influence Success of Steroid Injection in Trigger Finger. Issue 2 (8th June 2022) - Hollins, Andrew W.; Hein, Rachel; Atia, Andrew; Taskindoust, Mahsa; Darner, Grant; Shammas, Ronnie; Mithani, Suhail K.
Abstract : Background: Trigger finger is one of the most common hand abnormalities, with a prevalence of 2 percent of the general population. Conservative treatment with corticosteroid injections at the A1 pulley has been shown to be a cost-effective first-line treatment. However, additional patient factors have not fully been described regarding steroid injection efficacy. The authors hypothesize that patients presenting with longer chronicity of symptoms before treatment and elevated blood glucose would have reduced success rates of steroid injection therapy. Methods: A retrospective chart review of 297 patients at a single institution was performed between 2013 and 2019. Patients were included if they presented with the diagnosis of trigger finger and were treated with initial corticosteroid injection at the A1 pulley. Results: Steroid injection therapy alone was successful in 65 percent of patients. Patients received on average of 1.61 steroid injections. Patients who failed treatment received an average of 1.85 injections compared to 1.49 for those who had successful corticosteroid injection therapy ( p = 0.001). Presence of ipsilateral hand disease was associated with significant increase in failure of steroid injections (43.4 percent versus 30.8 percent; p = 0.032). Diabetic patients with hemoglobin A1c levels greater than 6.5 percent had a significantly higher rate of failing steroid injection therapy (71.9 percent versus 38.1 percent; p < 0.001). Patients who presented with greater than 2.5 months of symptoms had a higher failure rate of corticosteroid therapy (40.4 percent versus 29.5 percent; p = 0.048). Conclusion: Patients with a coexisting diagnosis of diabetes and a hemoglobin A1c level greater than 6.5 percent, ipsilateral concomitant hand disease, or presence of symptoms for greater than 2.5 months should be counseled regarding higher risk of failure of local corticosteroid injection. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.